Residu Antibiotik Tetrasiklin dan Penisilin dalam Daging Sapi Bali yang Diperdagangkan di Beberapa Pasar di Bali (TETRACYCLINE AND PENILILLIN ANTIBIOTIC RESIDUES IN BALI BEEF WHICH ARE TRADED IN SEVERAL MARKETS IN BALI) - Siswanto, Siswanto; Sulabda, I Nyoman (Jurnal Veteriner; Vol 19 No 4 (2018)DO - 10.19087/jveteriner.2018.19.4.497, 2019)
Animal products that are marketed are found to contain antibiotics (residues), so that if consumed by the humans for a long time will have a negative effect on human health, therefore regular monitoring is needed. Therefore it is very important to do the research on antibiotic residues in beef in several market areas in Bali. This study aims to determine residual tetracycline and penicillin antibiotics on beef bali cattle in several markets in Bali-Indonesia.  Research using 60 samples of beef originated from 5 different markets in Bali. As many as 12 sempels (100 g for each sample) was taken from each market that were purchased from different merchants. Screening tests (bioassay test) used to determine antibiotic residues in meat. The results showed that only three samples were positive containing antibiotics there were tertrasiklin 2 samples (3.33%) and penicillin1sample(1.67%). It was concluded that there were still antibiotic residues in beef marketed  in Bali.
Keywords: Keywords: antibiotic residues, screening tests, beef, bali cattle.